2016
DOI: 10.1186/s12905-016-0349-8
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of complete colon structure in a mature cystic teratoma of the ovary in menopausal woman: a case report

Abstract: BackgroundMature cystic teratoma (MCT) of the ovary is benign germ cell tumor and shows the highest incidence in women of reproductive age. Histologically, it includes components derived from endoderm, mesoderm, and ectoderm. Although there have been many reports of MCT having small part of the intestinal component, ovarian MCT containing complete colon structure was very rare.Case presentationA 54-year-old woman underwent laparoscopic left salpingo-oophorectomy due to an incidentally found ovarian mass. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…Teratoma frequencies found in our study were in concordance with data review [13][14][15][16]. The most affected group was women in reproductive age, but children and menopausal women were also concerned.…”
Section: Discussion Epidemiologysupporting
confidence: 91%
See 2 more Smart Citations
“…Teratoma frequencies found in our study were in concordance with data review [13][14][15][16]. The most affected group was women in reproductive age, but children and menopausal women were also concerned.…”
Section: Discussion Epidemiologysupporting
confidence: 91%
“…The prevalence rate of 20% of all ovarian neoplasms and the mean age of 31 years were in line with data of literature. Indeed, MCOT accounts for 10% to 20% of all ovarian adult neoplasms with approximately mean age of 27 years [4,14,15] and it represents 60% to 70% of all benign ovarian tumours [3,16].…”
Section: Discussion Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…This incidence is consistent with the occurrence of GI-type epithelium with or without other components in MCTs, which has been reported to be 7-13% (6,13). Totally organized GI tracts within ovarian MCTs are rare, with <20 previously reported cases (8)(9)(10)(11)(12). The present study revealed GI tract-like structures containing mucosa, MM, muscular walls and serosa in 3 (2.4%) of 126 MCT cases, and muscular walls without mucosa in 4 (3.2%) cases.…”
Section: Discussionmentioning
confidence: 75%
“…Thyroid tissues, salivary glands and ependymal tissues are occasionally present. Gastrointestinal (GI) epithelium and organized GI tracts may be observed in MCTs (5)(6)(7)(8)(9)(10)(11)(12). To date, only two previous articles (11,12) have described interstitial cells of Cajal (ICC) within the GI tract-like muscular walls in three sporadic cases of MCT.…”
Section: Introductionmentioning
confidence: 99%